Excitation-intensity-dependent charge carrier dynamics in thienylenevinylene-phthalimide copolymer based thin polymer films. (20th April 2015) - Kim, In-Sik; Kwon, Sunghoon; Kim, Juhwan; Kim, Dong-Yu; Ko, Do-Kyeong
Abstract: The ultrafast charge carrier dynamics of alkyl-substituted thienylenevinylene and phtalimide-based donor/acceptor (D/A) alternating copolymer (PTVPhI-Eh) as well as PTVPhI-Eh:PC71 BM bulk heterojunctions (BHJs) with and without processing 1-chloronaphthalene (CN) additive have been studied by means of a femtosecond transient absorption (TA) measurement. Photo induced absorption of the D/A copolymer was prohibited under certain excitation intensity. In both BHJs, we observed fast decay components (∼1 ps) which are assisted by high order process such as exciton-charge annihilation (ECA) or exciton–exciton annihilation (EEA) under high excitation intensity. In the CN-treated BHJ, however, the fast decay components were shortened to <1 ps because of increased ECA or EEA rate. In addition, the CN-treated BHJ showed slow geminate recombination time which indicates reduced carrier loss. Consequently, we could confirm excited stated properties of the copolymer and ultrafast spectroscopic evidences of enhancement in power conversion efficiency related with the inclusion of solvent additive to BHJ. Graphical abstract: Highlights: We examine first femtosecond measurement on specific copolymer films. Effect of processing additive on copolymer:fullerene bulk heterojunction film is spectroscopically revealed. We take advantage of carrier annihilation to uncover small changes in charge carrier dynamics of the copolymer films. Our results will broaden the knowledge on solar cell performance based on a donor-acceptor alternating copolymer.